The main forest species encountered in southern and central Benin, West Africa - GANGLO, COSSI JEAN; KOURA, Koura; AÏKPON, Gorgias (My University, 2024)
The dataset provides information on forest species found in southern and central Benin, West Africa. This dataset is extremely useful for forestry research, as it focuses mainly on the various forest species of major importance. It can be used as a basis for characterising individuals or populations of species, based on their abundance in relation to anthropogenic pressure and changes in environmental conditions. These species are characteristic of forests and, above all, are of particular interest both to populations and to managers of protected areas. Field collections were initiated in 2007 as part of natural forest inventory work. The data collected have been completed by various field works that followed this work on forest species in southern Benin. The latest version of the dataset is publicly and freely accessible on the GBIF website at the address https://www.gbif.org/dataset/aff3a10a-a86b-4eff-98e4-d63f92fd6f7e
Keywords: dataset; biodiversity; forest species; southern Benin; west Africa